2017
DOI: 10.1002/hed.24912
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcomes for stage‐matched endoscopic and open resection of olfactory neuroblastoma

Abstract: Stage-matched survival was better for the endoscopically treated group compared to the open surgery group, with high negative margin resections obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 30 publications
3
65
0
2
Order By: Relevance
“…However, EER showed better local control, better survival, and less morbidity . In a recent study, stage‐matched patients had a better survival with an endoscopic approach than open surgery especially in Kadish C patients . In our series, seven patients were treated with EER resulting only in two complete histological resections.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, EER showed better local control, better survival, and less morbidity . In a recent study, stage‐matched patients had a better survival with an endoscopic approach than open surgery especially in Kadish C patients . In our series, seven patients were treated with EER resulting only in two complete histological resections.…”
Section: Discussionmentioning
confidence: 64%
“…25 In a recent study, stage-matched patients had a better survival with an endoscopic approach than open surgery especially in Kadish C patients. 26 In our series, seven patients were treated with EER resulting only in two complete histological resections. Hence, EER is promising especially in children in order to decrease the morbidity of CFR, but clinicians also have to focus on occult dural involvement that may be the origin of relapse.…”
Section: Discussionmentioning
confidence: 87%
“…ENB is a rare primary malignancy of the sinonasal cavity, with an estimated overall 5-year survival being reported between 62% to 86%. [11][12][13] Although advances in endoscopic endonasal approaches and radiotherapy have improved treatment options for patients, risk of locoregional or distant treatment failure remains high for some years following initial treatment. Prior studies have suggested that the presence of cervical lymph node metastases negatively impacts overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of obtaining negative margins for locoregional control and overall survival cannot be overstated. Multiple studies demonstrate that positive margins predict treatment failure and negatively impact survival . En bloc resection, in contrast to piecemeal resection, has been the traditional surgical method to obtain negative margins.…”
Section: Marginsmentioning
confidence: 99%
“…Multiple studies demonstrate that positive margins predict treatment failure and negatively impact survival. 7,9,10 En bloc resection, in contrast to piecemeal resection, has been the traditional surgical method to obtain negative margins. Violation of the cancer via debulking was believed to spread cancer and reduce locoregional control and survival.…”
Section: Marginsmentioning
confidence: 99%